Upwelling : mechanisms, ecological effects and threats to biodiversity - Fischer, Williams E.; Green, Adams B. (Oceanography and ocean engineering, 2013)
An upwelling is a rise of deep sea waters to the surface. A minimum of four types of upwelling have been identified: coastal upwelling; large-scale wind-induced upwelling in the open ocean; upwelling related to tropical cyclones; and upwelling related to topography. In this book, the authors present current research in the study of the mechanisms, ecological effects and threats to biodiversity due to upwelling. Topics discussed in this compilation include the ecological effects of coastal upwelling in Cabo Frio, Rio de Janeiro, Brazil; Namibian upwelling and its effects on macrozoobenthic dive.